Paleo-Tethys subduction and arc-continent collision: Evidence from zircon U-Pb chronology, geochemistry and Sr-Nd-Hf isotopes of eclogites in western Yunnan, bangbing area, southeastern Tibetan Plateau - Fu, Yuzhen; Peng, Zhimin; Wang, Guozhi; Hu, Jingfeng; Zhang, Zhang; Guan, Junlei; Ren, Fei (Frontiers in Earth Science, 2022)
The Changning-Menglian suture zone (CMSZ) in the southeastern Tibetan Plateau is a newly discovered HP-UHP metamorphic zone. The eclogites therein are the key evidence constraining the main suture of the Proto- and Palaeo-Tethys Ocean in western Yunnan. Targeting the weakly studied Bangbing eclogites, we developed a comprehensive study on the whole-rock compositions, Sr-Nd isotope and zircon U-Pb ages, zircon trace elements and Lu-Hf isotope to reveal the subduction and arc-land collision. The eclogites occur as massive blocks or lenses and embedded in garnet phengite quartz schists of Lancang Group, Early Palaeozoic accretionary complex. Their geochemistry is similar to E-MORB, and exhibit isotopic εNd(t) values of 3.14–4.49 and εHf(t) of 14.64–16.41, respectively. The Nb-enriched mafic protoliths suggested they were probably generated by partial melting of the enriched oceanic asthenospheic mantle within the spinel stability field and emplaced emplaced or erupted as mid-ocean ridge in the Paleo-Tethys Ocean. By LA-ICP-MS zircon U-Pb age testing, the magmatic zircon grains separated from the eclogites yield a wide range of ages, which may be capture zircon ages rather than protolith crystallization. We infer the age of eclogite-facies metamorphism to be 238 ± 2 Ma based on CL images, zircon trace element analysis, and that this metamorphism marks the collision between the Eastern Lincang magmatic arc, the Simao block and the Western Baoshan block. Thus, exhumation of the eclogites occurred only 7 to 23Ma later, according to age 231-215 Ma for post-collisional volcanic and granitic rocks east of the CMSZ. Conclusively, the continued subduction of the Palaeo-Tethys oceanic crust occurred during the Early-Middle Triassic, and rapid exhumation in the Late Triassic. The Changning-Menglian suture zone is a typical oceanic subduction-accretionary orogeny belt.